2020
DOI: 10.1177/8755293020957338
|View full text |Cite
|
Sign up to set email alerts
|

Exploring probabilistic seismic risk assessment accounting for seismicity clustering and damage accumulation: Part I. Hazard analysis

Abstract: Probabilistic seismic hazard analysis (PSHA), as a tool to assess the probability that ground motion of a given intensity or larger is experienced at a given site and time span, has historically comprised the basis of both building design codes in earthquake-prone regions and seismic risk models. The PSHA traditionally refers solely to mainshock events and typically employs a homogeneous Poisson process to model their occurrence. Nevertheless, recent disasters, such as the 2010–2011 Christchurch sequence or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…In MPS19 we use GK74 declustering technique, because it is the most efficient procedure to get a mainshocks distribution similar to Poisson distribution (see Section 3). No matter of the declustering method used, this operation implies that strong ground shaking caused by aftershocks and foreshocks is not considered in classical PSHA [Boyd, 2012;Iervolino et al, 2012;Marzocchi and Taroni, 2014] and risk [Papadopoulos et al, 2020]. For this reason, we build a version of MPS19 which includes the effects of earthquake clustering (hereafter MPS19_cluster) and allows us to quantify its impact in terms of seismic hazard.…”
Section: The New Italian Seismic Hazard Modelmentioning
confidence: 99%
“…In MPS19 we use GK74 declustering technique, because it is the most efficient procedure to get a mainshocks distribution similar to Poisson distribution (see Section 3). No matter of the declustering method used, this operation implies that strong ground shaking caused by aftershocks and foreshocks is not considered in classical PSHA [Boyd, 2012;Iervolino et al, 2012;Marzocchi and Taroni, 2014] and risk [Papadopoulos et al, 2020]. For this reason, we build a version of MPS19 which includes the effects of earthquake clustering (hereafter MPS19_cluster) and allows us to quantify its impact in terms of seismic hazard.…”
Section: The New Italian Seismic Hazard Modelmentioning
confidence: 99%
“…As already pointed out, the seismic hazard component employed here is modeled through the space–time ETAS model. As explained in Papadopoulos et al (in press) but reported here for convenience, the latter is a self-exciting point process (Hawkes, 1971) essentially based on the principle that each earthquake can trigger its own offspring. The conditional intensity, that is, the infinitesimal expected occurrence rate at a specific point in space and time, according to the ETAS model can generally be formulated as follows:…”
Section: Seismic Hazard Modelmentioning
confidence: 99%
“…As discussed in the companion paper (Papadopoulos et al, in press), fixing the parameter α equal to β in the ETAS model (as done for the second, fourth, fifth, and sixth ETAS parameterizations in Table 1) compensates for some sources of bias but may occasionally result in unrealistic sequence realizations. Within the context of operational earthquake forecasting, where the ETAS model has been heavily used, this might not be important, given that the main product is daily predictions of the number of earthquakes, typically given as a mean/median point estimate along with a confidence interval (both of which are not overly affected by the extreme tails of the distribution).…”
Section: Seismic Hazard Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review of these methods is provided in Iacoletti et al (2021). Short-term time-dependent seismic hazard assessments account for the spatial and temporal clustering of aftershock events that follow the occurrence of a J o u r n a l P r e -p r o o f Journal Pre-proof mainshock earthquake (e.g., Papadopoulos et al, 2020).…”
Section: Modelling Of Future Non-climate-related Hazardsmentioning
confidence: 99%